Giant superconducting fluctuations in the compensated semimetal FeSe at the BCS–BEC crossover - S. Kasahara (Nature Portfolio, 2016)
The crossover between the weak-coupling limit and strong-coupling limit provides important information for quantum bound states of interacting fermions. Here, Kasahara et al. report thermodynamic evidence for prevailing phase fluctuations of superconductivity, highlighting unusual normal state in the BCS-BEC crossover regime.